A major role for carbon monoxide as an endogenous hyperpolarizing factor in the gastrointestinal tract - Farrugia, Gianrico (National Academy of Sciences, 2003)
Carbon monoxide (CO) is proposed as a physiological messenger. CO activates cGMP and has a direct effect on potassium channels. Both actions of CO lead to hyperpolarization of a cell's resting membrane potential, suggesting that CO may function as a hyperpolarizing factor, although direct evidence is still lacking. Here we take advantage of the known membrane potential gradient that exists in the muscle layers of the gastrointestinal tract to determine whether CO is an endogenous hyperpolarizing factor. We find that heme oxygenase-2-null mice have depolarized smooth muscle cells and that the membrane potential gradient in the gut is abolished. Exogenous CO hyperpolarizes the membrane potential. Regions of the canine gastrointestinal tract that are more hyperpolarized generate more CO and have higher heme oxygenase activity than more depolarized regions. Our results suggest that CO is a critical hyperpolarizing factor required for the maintenance of intestinal smooth muscle membrane potential and gradient.